Educational Marketing Strategies to Increase Student Enrollment in Catholic Private Schools in Tangerang City and West Jakarta City - Anastasia Aprilia Festi Setyastuti; Mada Sutapa (International Forum of Researchers and Lecturers, 2026)
Educational institutions increasingly face competitive pressures in attracting and maintaining student enrollment, particularly within the private school sector. This study examines educational marketing strategies implemented to increase student enrollment in Catholic private schools. The research focuses on two institutions, namely SMA Strada Santo Thomas Aquino and SMA Katolik Lia Stephanie, which demonstrate different enrollment trends and marketing approaches. A qualitative exploratory method was employed to understand institutional strategies and marketing practices in their natural contexts. Data were collected through observation, semi-structured interviews, and documentation conducted between August and December 2025. Data validity was ensured through source and technique triangulation, while analysis followed the Miles, Huberman, and Saldana model consisting of data condensation, data display, and conclusion drawing. The findings reveal that both schools implement educational marketing strategies based on the marketing mix framework (7P), including product, price, place, promotion, people, process, and physical evidence. SMA Strada Santo Thomas Aquino applies a community-relational approach that emphasizes Catholic values, alumni loyalty, school reputation, and word-of-mouth communication within community networks. SMA Katolik Lia Stephanie adopts a differentiation-professional approach by offering flagship academic programs, modern facilities, and structured promotional strategies coordinated by a dedicated marketing team. The effectiveness of these strategies is supported by church networks, alumni engagement, foundation support, and consistent educational service quality. Several challenges were identified, including limited marketing resources, insufficient digital marketing competence, and increasing competition among private schools. Strengthening adaptive and innovative marketing strategies is essential for maintaining institutional competitiveness and sustaining student enrollment in Catholic private educational institutions.